Ynthesis and Characterization of 1-Aryl-5-hepta-O-acetyl-β-D-maltosyl-2-S-benzyl-2, 4-isodithiobiurets. Issue 1 (2012) - Ghuge, R. D.; Deshmukh, S. P.
Abstract : The facile synthesis of 1-aryl-5-hepta- o -acetyl- β-D -maltosyl-2- S -benzyl-2, 4-isodithiobiurets (IIIa-g) has been achieved by the interaction of 1-hepta- O -acetyl- β–D -maltosyl isothiocyanate (I) with various1-aryl- S -benzyl isothiocarbamides (IIa-g) . All the newly synthesized N -maltosylated compounds characterized by elemental analysis, IR, NMR and Mass spectral studies.